2016
DOI: 10.1080/14737175.2016.1200973
|View full text |Cite
|
Sign up to set email alerts
|

Chronic migraine treatment: from OnabotulinumtoxinA onwards

Abstract: Our goal is to review the existing data on OnabotulinoumtoxinA and CGRP-targeting drugs such as anti-CGRP monoclonal antibodies, one of the most promising migraine drugs under development. The research of bibliographic databases has included only published peer-reviewed articles from indexed journals. Expert commentary: To date, real-life studies are supporting OnabotulinumtoxinA in the treatment of chronic migraine. Additionally, anti-CGRP mAbs showed good efficacy and safety in recent RCTs and may soon contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 112 publications
1
15
0
Order By: Relevance
“…Efficacy of OnabotA in our series was also similar as it was described in studies in a real-life setting [815]. …”
Section: Discussionsupporting
confidence: 86%
“…Efficacy of OnabotA in our series was also similar as it was described in studies in a real-life setting [815]. …”
Section: Discussionsupporting
confidence: 86%
“…However, liver toxicity with their daily administration was found. Thus further developments of some CGRP-RAs including telcagepant MK-0974 and MK-3207 were terminated [1820, 55], two CGRP-RAs, B144370A and BMS-927711, showed a good clinical efficacy in the phase II studies but their development status is not clear and it is not known whether these drugs showed liver toxicity [52, 54], and ubrogepant MK-1602, has been tested in two phase II trials, but the results have not been reported yet [55]. CGRP-mAbs are macromolecules made of proteins that directly target CGRP or its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…WHO ranks migraine as the sixth highest cause of disability worldwide when considered alone, and the third highest when MOH is included [5]. According to U.S. figures, the total annual median cost for medical services and analgesics for the relief of migraine, low back pain, and fibromyalgia is roughly $5,000 and more than $25,000 for treating HIV-related pain and multiple sclerosis [6].…”
Section: Introductionmentioning
confidence: 99%